2015
DOI: 10.1155/2015/360730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Extract fromMorinda officinalis F. C. Howon Microwave-Induced Hypothalamic-Pituitary-Testis Axis Impairment in Male Sprague-Dawley Rats

Abstract: The present study aimed to assess the protective effects of aqueous extract from Morinda officinalis F. C. How on microwave-induced reproductive impairment in male rats. Microwave exposure injury was induced by exposure of 900 MHz microwaves at 218 μm/cm2radiation densities, 24 hours/day for 10 days. Male Sprague-Dawley rats were randomized to: normal control, microwave exposure model, or water layer or ethyl acetate layer of aqueous extract 40 g/kg treatment groups. After 2 weeks of treatment, sexual performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…Therefore, we needed to identify the most effective ingredient in M. officinalis to promote fertility and avoid its toxicity. Combining previous studies from our laboratory [4, 5] with other related studies, we speculated that MOP may be the most effective component and the present study confirmed this hypothesis. Indeed, the results showed that MOP can repair the impaired male reproductive system caused by varicocele.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, we needed to identify the most effective ingredient in M. officinalis to promote fertility and avoid its toxicity. Combining previous studies from our laboratory [4, 5] with other related studies, we speculated that MOP may be the most effective component and the present study confirmed this hypothesis. Indeed, the results showed that MOP can repair the impaired male reproductive system caused by varicocele.…”
Section: Discussionsupporting
confidence: 89%
“…M. officinalis Polysaccharide (MOP), the main bioactive chemical component of M. officinalis (accounting for 10.55–35% of the total weight) of different origins in China [2, 3] has many biological activities, including antitumor, antisenility, and antiviral activities as well as enhancing immunity and scavenging free radical. Our previous study indicated that M. officinalis aqueous extract (containing most of the MOP) was more effective than the alcohol extract in promoting spermatogenesis and encouraging the plerosis of injured reproductive organs [4, 5], indicating that MOP may be the main effective component that tonifies the kidney and strengthens yang in M. officinalis .…”
Section: Introductionmentioning
confidence: 99%
“…Thence, we surmised that MON and DA may be able to exert their pharmacological effects in these target organs. MO strengths kidney- yang and improves spermatogenesis and the reproductive capacity [23, 24], which is consistent with our finding that MON and DA distributed in the testes at a high concentration. MO and MON showed an obvious anti-osteoporosis effect [10, 11], which is consistent with our finding that MON and DA were also observed in the ovary, uterus and bone marrow at a high concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Administration of M. officinalis extract protects the membrane of human sperm suspension from oxidative injury (Yang, Zhang, Ding, Yan, & Du, ). The aqueous extract of M. officinalis increases sperm count and germ cell numbers in the seminiferous tubules of rats (Song, Wang, & Wang, ; Wang et al, ). Spermatogenesis was improved, and the secretion of GnRH was stimulated in experimental varicocele rats treated with water‐soluble polysaccharides obtained from M. officinalis (Zhang, Hao, Wang, Lin, & Wang, ; Zhu et al, ; Zhu, Zhao, Huang, Wang, & Wang, ).…”
Section: Morinda Officinalismentioning
confidence: 99%
“…Additional study by Song et al () observed that the sexual performance of the animals was improved and their sperm numbers both in the testis and in the epididymis were increased. The hormonal profiles of these animals were characterised by high testosterone level along with decreased LH and GnRH levels (Song et al, ). Furthermore, experimental rat models showing impaired spermatogenesis by intraperitoneal injection of cytoxan were also repaired in a dose‐dependent manner by extract of M. officinalis (Chen & Wang, ).…”
Section: Morinda Officinalismentioning
confidence: 99%